2016
DOI: 10.3892/ol.2016.4157
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of ALK gene fusions in lung cancer using the differential expression and exon integrity methods

Abstract: Abstract. Anaplastic lymphoma kinase (ALK) gene fusion is a driving mutation underlying the development of non-small cell lung cancer (NSCLC). Accurate detection of ALK fusion is critical for the use of ALK inhibitors in the treatment of NSCLC. Commonly utilized methods for ALK detection include fluorescence in situ hybridization (FISH) and immunohistochemistry (IHC). However, these methods are time-consuming and costly. In the present study, a method for assessing ALK gene fusion based on the differential exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Notably, although lacking the 5′ acceptor splice site of ALK exon 20, the actual transcript of case #P2008280124 excluded partial nucleotides and retained a portion of exon 20 through an alternative splicing signal at the RNA level rather than implementing exon skipping splicing and it resulted in two different variants (E19; del14A20 and E19; del20A20). Further comparative analysis of the transcripts and the amino acid sequences showed that partial retention of exon 20 could ensure the in‐frame sequence with integrity of the ALK kinase domain [ 43 , 44 ]. Patients harbouring multiple EML4‐ALK variants implied a poor prognosis due to the high heterogeneity in the tumour tissue [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, although lacking the 5′ acceptor splice site of ALK exon 20, the actual transcript of case #P2008280124 excluded partial nucleotides and retained a portion of exon 20 through an alternative splicing signal at the RNA level rather than implementing exon skipping splicing and it resulted in two different variants (E19; del14A20 and E19; del20A20). Further comparative analysis of the transcripts and the amino acid sequences showed that partial retention of exon 20 could ensure the in‐frame sequence with integrity of the ALK kinase domain [ 43 , 44 ]. Patients harbouring multiple EML4‐ALK variants implied a poor prognosis due to the high heterogeneity in the tumour tissue [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the clinical application of specific RT-PCR assays has been limited by the number of reactions and the large quantity of clinical samples required to investigate the different ALK fusions. Previously, Huang et al (23) demonstrated, both on NSCLC tissue samples and on cell-free urine samples, the efficacy of a differential expression method, based on the presence of aberrant high levels of the ALK kinase domain (23). Notably, the predominant pathological consequence of ALK fusion in tumor cells is its aberrant expression, regardless of the fusion partner.…”
Section: A B C D E Fmentioning
confidence: 99%